2017
DOI: 10.1021/acs.energyfuels.7b01793
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Separation of Phenolic Compounds from Oil Mixtures by Imidazolium-Based Dicationic Ionic Liquids via Forming Deep Eutectic Solvents

Abstract: The separation of phenolic compounds from oil mixtures is an important step for further refining or applications of the oil mixtures. In this work, three imidazolium-based dicationic ionic liquids (DILs; 1,2-bis[N-(N′-methylimidazolium)]ethane dibromide, DIL1; 1,3-bis[N-(N′-methylimidazolium)]propane dibromide, DIL2; and 1,4-bis[N-(N′methylimidazolium)]butane dibromide, DIL3) were synthesized and used to separate phenolic compounds from oil mixtures. The effects of time, temperature, DIL:phenol mole ratio, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…a Youan et al (2017) .b Priede et al (2014) .c Zhang et al (2018) .d Lee et al (2010) .e Yang et al (2014) .f Lee et al (2011) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a Youan et al (2017) .b Priede et al (2014) .c Zhang et al (2018) .d Lee et al (2010) .e Yang et al (2014) .f Lee et al (2011) .…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain further information on these ionic media, which have already been used in few applications [e.g., in situ formation of DESs in an innovative procedure for the separation of phenols from oils (Youan et al, 2017, 2018), CO 2 cycloaddition reaction (Liu et al, 2015), elucidation of a reaction mechanism (Bortolini et al, 2014)] or could be used to develop stimuli responsive ionic polymers, a systematic investigation of a homogeneous class of 12 imidazolium based dicationic dibromides and related dicarboxylate salts has been performed. The thermal properties of this latter class of compounds were also compared to mono cation derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The main advantage in using DILs instead of the corresponding ILs lies in the possibility of further modulating their properties varying the nature of the spacer. [4] In fact, imidazolium DILs have been successfully used as electrolytes in dye sensitized solar cells (DSSCs), [5] as efficient replacements of organic phase-change materials (the heat capacity of DILs is noteworthy higher than that of the corresponding monocations), [6,7] as solvents for the controlled pyrolysis of cellulose, [8] as templates for the synthesis of ZnO nanostructures in water, [9,10] as surfactants (due to a better capacity of aggregation with respect to monocationic analogues), [11] as efficient extractors of phenolic compounds from oil mixtures [12] or of triazole fungicides from contaminated water, [13] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the antioxidants contained in the Anethum graveolens extracts were able to giving hydrogen to a free radical to eliminate potential damage. In another work, the separation of phenolic compounds from oil mixtures by three imidazoliumbased dicationic ionic liquids was investigated by Wu et al [16]. 1,4-bis[N-(N′methylimidazolium)]butane dibromide demonstrated the maximum phenol removal yield of 96.6% within 5 min.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%